A spatiotemporal analysis of fire incidents in Manila from 2011-2016: Implications for fire prevention. Issue 2 (27th November 2018) - Bringula, Rex; Balahadia, Francis
Abstract : Purpose: The purpose of this paper is to report the results of spatiotemporal analysis of the 3, 506 fire incidents in the city of Manila from 2011 to 2016. Design/methodology/approach: A spatiotemporal and statistical analysis was carried out to determine the pattern of fire incidents in the city of Manila. Findings: Fire incidence in Manila did not exhibit any pattern in terms of time, day of the week or month of the year. However, fire incidence did exhibit a pattern in terms of location. Faulty electrical connections are the major cause of fires throughout the year and throughout the 14 municipalities of Manila. Thus, the null hypothesis stating that spatiotemporal characteristics of cases of fire in the city of Manila do not exhibit a pattern is partially rejected. Research limitations/implications: Future studies may investigate the influence of building maintenance, government control, and cooking and cigarette-disposal behaviors on fire occurrence. It is recommended that the study be replicated in other cities of Metro Manila. Practical implications: Based on the causes and the spatiotemporal characteristics of fires, stakeholders (e.g. government, Bureau of Fire Protection, local government units (LGUs), communities and residents) can be informed about how to prevent fires. LGUs and government agencies can utilize the findings of this study in developing fire prevention programs for the municipalities with the highest incidence of fires. Originality/value: These findings can serve as a basis for policy formulation and as a reference for the allocation of fire prevention resources and for the literature on strategic planning for fire prevention in Manila.